A Microeconometric Characterisation of Household Consumption Using Quantile Regression - Gerd Ronning; Niels Schulz (Institut für Angewandte Wirtschaftsforschung (IAW), 2002)
The paper uses micro cross-section data from the GfK consumer panel for econometric demand analysis of private households in Germany. Contrary to most research which considered behavior we extend this approach to consumer behavior for di®erent of consumption. Our analytical tool is quantile regression which allows us to describe the conditional distribu- tion for any quantile including the (conditional) median representing behavior. As an illustrative example we use the demand for beer and wine. The paper shows quite distinct patterns regarding price and income e®ects for di®erent goods which leads us to an extended characterization of household demand.
Keywords: C21; C49; D12; 330; econometric demand analysis; Engel curve; demand system; micro data; Konsumentenverhalten; Mikroökonomische Konsumfunktion; Regression; Schätzung; Bier; Wein; Theorie; Deutschland; Konsumklima